2005
DOI: 10.1177/08830738050200070201
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Intellectual Outcome After Arterial Ischemic Stroke and Sinovenous Thrombosis in Childhood and Infancy

Abstract: Arterial ischemic stroke is approximately four times more prevalent than sinovenous thrombosis and has been associated with a worse neurologic outcome than sinovenous thrombosis; however, no data are available comparing intellectual outcome after pediatric arterial ischemic stroke and sinovenous thrombosis. We report the short-term intellectual outcome (mean 5.8 months since stroke) in a sample of 72 children, 47 with arterial ischemic stroke, and 25 with sinovenous thrombosis. Intellectual outcome measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 43 publications
(58 reference statements)
5
49
1
6
Order By: Relevance
“…Moreover, due to our prospective study design and lack of intelligence measures for the youngest age group, it was necessary to include a developmental measure as an outcome measure. However, taking into account the result of a previous study, 38 which did not find any age at stroke effect, although their youngest age group was exclusively tested with the BSID-II, we argue that our finding that the early age group showed the worst cognitive outcome cannot solely be due to the use of the BSID-II. Moreover, the youngest children in our study with NI and a low cognitive outcome might be prone to a "growing into deficit" and therefore may have increasingly significant cognitive deficits with time.…”
Section: Neurology 82 March 4 2014mentioning
confidence: 64%
“…Moreover, due to our prospective study design and lack of intelligence measures for the youngest age group, it was necessary to include a developmental measure as an outcome measure. However, taking into account the result of a previous study, 38 which did not find any age at stroke effect, although their youngest age group was exclusively tested with the BSID-II, we argue that our finding that the early age group showed the worst cognitive outcome cannot solely be due to the use of the BSID-II. Moreover, the youngest children in our study with NI and a low cognitive outcome might be prone to a "growing into deficit" and therefore may have increasingly significant cognitive deficits with time.…”
Section: Neurology 82 March 4 2014mentioning
confidence: 64%
“…Neurologic outcome after childhood arterial ischemic stroke has been reported by several groups [67][68][69]. Outcome after HS, however, has not been well studied in children.…”
Section: Neurologic Outcome and Hs Recurrencementioning
confidence: 99%
“…The majority of studies reporting cognitive 26,39,40 and functional 41,42 outcomes after childhood stroke have not assessed the influence of risk factors or pathogenesis on outcome. A recent Swiss multicentre study, however, found no association between risk factors and cognition.…”
Section: Cognitive Function After Childhood Aismentioning
confidence: 99%